Value-Based Inventory Management - Grzegorz Michalski (Romanian Journal of Economic Forecasting, 2008)
The basic financial purpose of a firm is to maximize its value. An inventory management system should also contribute to realization of this basic aim. Many current asset management models currently found in financial management literature were constructed with the assumption of book profit maximization as basic aim. However these models could lack what relates to another aim, i.e., maximization of enterprise value. This article presents a modified value-based inventory management model.
Keywords: G32; G11; M11; D81; O16; P33; P34; 330; Inventory Management; Value based management; free cash flow; working capital management; short-run financial management